The Study of Figurative Languages using Stylistics Theory in What My Mother Doesn’t Know by Sonya Sones - Winnie, Winnie; Akun, Akun (Lingua Cultura, 2008)
What My Mother Doesn’t Know is a novel-in-verse by Sonya Sones which tells about a teenage girl named Sophie who tries to find her Mr. Right and her bad relationship with her parents. In the end, Sophie finds her Mr. Right who is actually not her type of boy friend but he can make her feel happy and even though she hates her parents, she realizes that she loves them nevertheless. The purpose of this article is to prove that the author’s use of style can reveal the themes of novel-in-verse The analysis of the novel-in-verse focuses mainly on the themes and the figurative language of simile, metaphor, personification, paradox, and hyperbole. Research methods are conducted in qualitative method in the form of library research and statistics to calculate how many poems use the five figurative languages and are related to the themes. In the analysis, the author’s style is figurative language and there are three themes that can be taken from the novel-in-verse. The themes are overwhelmed feeling does not show the true feeling, the bond of family will always be there, no matter how hateful we are to them and love is not determined by someone’s physical appearance. The result shows that 91.36 percents of poems that use the five figurative languages are related to the themes. It can be concluded that the author’s style in writing the novel-in-verse can reveal the three themes.